Female Representation on Banknotes: A Semiotic Analysis of 2022 Indonesia Banknotes - Michael Herdi Hadylaya (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2023)
Besides their economic value, banknotes have a symbolic value through an expression of cultural identity that forms a nation. Generally, the customary design of banknotes in most countries issued by financial authorities is the portrait of notable male leaders. This research examined the banknotes for the 2022 emission yearissued by Bank Indonesia to emphasize the frequent representation of male and female images used in the issued currency. Using the interpretivism paradigm with semiotic methods, this research found that on the surface, Indonesian banknotes in the 2022 emission year seem to show a sense of appreciation for women and femininity in Indonesia but in essence still lack a sense of justice towards women.